The Influence of Financial Literacy and Financial Technology on the Financial Performance of MSMEs (Case Study on MSMEs in Asia Mega Mas) : Pengaruh Literasi Keuangan dan Financial Technology terhadap Kinerja Keuangan UMKM (Studi Kasus pada UMKM di Asia Mega Mas) - Sharon Limvica; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study analyzes the influence of financial literacy and financial technology on the financial performance of MSMEs in the Asia Mega Mas Complex, Medan City. The research population consists of 95 MSMEs, with 60 samples obtained through purposive sampling. Data were collected using questionnaires and analyzed using IBM SPSS Statistics 25. The analysis includes validity and reliability testing, descriptive statistics, classical assumption tests, multiple linear regression, T – test, F – test , and the coefficient of determination (R²). The T – test results show that Financial Literacy significantly affects the Financial Performance of MSMEs, with T – Count is 5,067 > T – table is 2,00172 and a significance level of 0,000 < 0,05. Similarly, Financial Technology has a significant effect with T – Count is 5,856 > T Table 2,00172 and a significance level of 0,000 < 0,05. The F – Test indicates that both variables jointly influence MSME Financial Performance, with F – Count is 33,094 > F – Table value is 3,16 and a significance level of 0,000 < 0,05. The coefficient of determination (R²) is 0,537, showing that 53,7% of MSME Financial Performance is explained by Financial Literacy and Financial Technology, while 46,3% is affected by other factors not examined in this study.